DENTAL PRACTICE MANAGEMENT SOFTWARE IN THE ASSESSMENT OF TREATMENT NEEDS OF EDENTULOUS PATIENTS CANDIDATE TO IMPLANT-PROSTHETIC THERAPY - Doriana Agop-Forna; Cosmin Creţu; Norin Forna; Cristina Dascãlu; Claudiu Topoliceanu; Gholamreza Shokraei; Stratulat Matei Dana; Norina Forna (Romanian Society of Oral Rehabilitation, 2023)
Contemporary dental practice brings to our attention the presence of digital equipment in a large number of dental offices, which provides enhanced ergonomics and precision in achieving the current standards in this complex field, particularly in digital imaging. By utilizing digital applications in dental offices, dentists have the opportunity to make extremely precise diagnoses while reducing therapeutic procedures through an ergonomic approach. The purpose of this study is to individualize the manner in which digital applications in dental medicine can contribute to the therapeutic efficiency in each clinical case, offering a synthesis of accurate patient data and performed procedures at any given time. The digital application is structured based on patient data, treatment type, treatment plans, preventive procedures, prosthetic restorations, imaging area, as well as other categories that complement a successful therapeutic management. Software applications play an especially important role in optimizing both therapeutic management and the overall clinic where the software application is implemented as a daily approach. The data stored in software applications are extremely useful for both patients and doctors, providing a clear overview of the prevalence of procedures and materials used at any given moment. From the conducted statistical studies, we observe a prevalence of implantology and implant-prosthetic rehabilitation procedures, with a significant percentage of procedures falling within the realm of avant-garde preparations, such as augmentations using various types of Bio-oss and membranes, as well as a prevalence of sinus lift procedures for lateral areas.